Meningkatan Keterampilan Mahasiswa dalam Menulis Opini Berbasis Penggunaan Quora - Anhar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze, describe, enhance, and explore students' skills in writing opinions through the use of the digital platform Quora. It is important to note that opinion writing skills are crucial in academic, social, and professional contexts, as they require a comprehensive understanding, intellectual habits, and complex metacognitive abilities. With the rapid advancement of technology, the use of digital platforms in learning is expanding. Quora, as an interactive website, provides various resources to practice writing opinions, receive feedback, and develop the ability to think critically. This study employs a qualitative descriptive method. The subjects of this research are students Sekolah Tinggi Ilmu Ekonomi Balikpapan. The subjects of this research are first-semester students of the 2022/2023 academic year for Mata Kuliah Bahasa Indonesia. The results of the study indicate that the use of Quora is effective and significant in improving students' opinion writing skills. Students who are active on Quora can develop a more effective and persuasive writing style, receive constructive feedback, and help build a reputation in both academic and professional fields.